The benefit of molecular characterization during a measles upsurge in Denmark - Muscat, Mark; Vinner, Lasse; Christiansen, Annette Hartvig; Glismann, Steffen; Böttiger, Blenda Elisabeth (Vaccine, 2007)
Molecular characterization of measles virus was part of the epidemiological investigation of 27 measles cases reported in Denmark in 2006. RT-PCR detected measles virus RNA from various types of clinical specimens in 24 cases. Virus genotypes were determined by sequencing the nucleocapsid (N) gene. Four different genotypes, B3, D4, D5 and D9 were identified including two variants of the D4 genotype. In combination with the epidemiological data four clusters of measles cases and three sporadic cases were revealed. Our study showed that measles in Denmark resulted from imported measles virus strains. The limited duration and short chain of transmission of the identified clusters ascertain that the interruption of measles virus circulation is being sustained. However, measles transmission still has a potential to occur. To minimise the development of pools of susceptible individuals high (>/=95%) routine vaccination coverage with two doses of measles-containing vaccine needs to be attained. Molecular epidemiological studies have proved to be both a useful and a necessary component of an enhanced surveillance system required in the measles elimination phase.
Keywords: Denmark/epidemiology; Disease Outbreaks; Genotype; Humans; Measles/epidemiology; Measles virus/genetics; Molecular Epidemiology; Phylogeny; RNA, Viral/genetics